Recueil des sentences arbitrales, vol. XXIX - Nations Unies (United Nations, 2011)
The present volume consists of a collection of awards and similar decisions relating to a particular field of international law, namely the delimitation and demarcation of international boundaries. This volume contains awards handed down in 34 different dispute-settlement procedures over a period of more than 150 years, from the late 18th century to mid-20th century.